Nutrition counseling about general messages of balanced nutrition improve energy intake and haemoglobin level among HIV children - Waisaktini Maragareth; Eviyani Margaretha Manungkalit; Nia Kurniati; Utih Arupah (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2020)
ABSTRAKLatar Belakang: HIV adalah masalah kesehatan yang signiﬁ kan di Indonesia. satu kota di DKI Jakarta yang memiliki perkiraan jumlah kasus HIV tertinggi yang ditularkan melalui pria ke wanita. Beberapa penelitian menyatakan bahwa anak-anak dengan HIV memiliki asupan energi dan protein yang kurang, dan anemia. Oleh karena itu, pentingnya meningkatkan pengetahuan gizi seimbang pada orangtua yang memiliki anak HIV sehingga adanya peningkatan perilaku yang baik terhadap asupan makanan pada anaknya.Tujuan: Penelitian ini bertujuan untuk menganalisis pengaruh pemberian pedoman nutrisi seimbang pada asupan gizi (energi dan protein) dan kadar hemoglobin pada anak-anak HIV Metode: Desain penelitian adalah studi pra-eksperimental desain One Group Pre-Post Test. Penelitian ini adalah desain pre-post test kelompok kontrol non acak. Penelitian dilakukan di RSUPN dr Cipto Mangunkusumo dari Agustus hingga Oktober 2019. Sampel diambil secara purposive dengan kriteria inklusi dan eksklusi. Data dianalisis dengan menggunakan paired t-test.Hasil: Hasil penelitian menunjukkan bahwa ada perbedaan yang signiﬁ kan antara asupan energi rata-rata sebelum konseling dan setelah konseling (p = 0,013) tetapi tidak ada perbedaan yang signiﬁ kan antara asupan protein rata-rata sebelum dan sesudah konseling (p = 0,934). Ada perbedaan yang signiﬁ kan antara level Hb sebelum dan setelah konseling (p = 0,000).Kesimpulan: Ada pengaruh konseling gizi terhadap asupan energi tetapi tidak ada pengaruh terhadap kadar HbKATA KUNCI: energi; protein; Hb; HIV; anakABSTRACTBackground: HIV is a signiﬁ cant health problem in Indonesia. There were an estimated 242.699 persons living with HIV. Central Jakarta is one of the cities in DKI Jakarta that has the highest estimated number of HIV cases transmitted through men to women. Thus means that there is a possibility that the number of HIV children in Central Jakarta wil also increase. Some studies suggest that children with HIV have less energy and protein intake, and anemia. Because of this, the importance of increasing the knowledge of balanced nutrition in parents who have HIV children so that there is an increase in good behavior towards food intake in children. Objectives: The study aimed to analyze the effect of providing balanced nutrition guidelines on nutritional intake (energy and protein) and hemoglobin levels in HIV children. Methods: The research design was a pre-expreimental study of the One Group Pre-Post Test design. study was experimental non randomized control group pre-post test design. The study was carried out at RSUPN dr Cipto Mangunkusumo from August to October 2019. The sample were taken purposively with inclusion and exclusion criteria. Data were analyzed by using paired t-test.Results:The results showed that there was a signiﬁ cant difference between the mean energy intake before counseling and after counseling (p = 0.013) but there was no signiﬁ cant difference between the average protein intake before and after counseling (p = 0.934). There was a signiﬁ cant difference between the level Hb before and atter counseling (p = 0.000).Conclusions: The provision of counseling on nutrition guidelines provide a signiﬁ cant difference between the average energy intake and the levels of Hb.KEYWORDS: energy; protein; Hb; HIV; children